Pharmacokinetics of the novel cephalosporin cefepime (BMY-28142) in rats and monkeys. - Forgue, S T (1987)
The disposition of the novel cephalosporin cefepime (BMY-28142) was characterized for intravenous administration of single doses to rats and cynomolgus monkeys, the species used most extensively for safety evaluation of the compound. Serial blood samples were collected from individual animals, and plasma was analyzed for intact cefepime by a high-pressure liquid chromatography-UV method. Assay results were evaluated by compartmental and noncompartmental methods to characterize pharmacokinetics for each species and dosage regimen. For intravenous (i.v.) bolus administration of 28 to 386 mg/kg (body weight) to rats, total body clearance (CL; 11.0 ml/min per kg) was essentially invariant with the dose; however, the terminal half-life (t1/2) and the steady-state distribution volume (Vss) increased with increasing dose level. After administration of 87 to 1,502 mg/kg by i.v. infusion, CL (12.5 ml/min per kg) was again similar for all dose groups. Mean t1/2 values (1.3 to 4.6 h) appeared unusually long for a cephalosporin in rats, and inordinately variable. No consistent differences among dose group mean Vss values were found. The maximal concentration of drug in plasma at the end of infusion was not a linear function of dose. For the cynomolgus monkey, kinetic parameters for 5-min i.v. infusions were linearly related to dose over the range of 10 to 600 mg/kg. Mean parameter values were t1/2 = 1.7 h, CL = 1.6 ml/min per kg, and Vss = 0.21 liters/kg. The pharmacokinetic results indicate substantive differences between the two species with respect to their response to toxicologic doses of cefepime.